(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Тhe antioxidant activity (AOA) and phenolic content of Hypholoma fasciculare, Agaricus bisporus, Pleurotus ostreatus, Trichaptum abietinum, Polyporus squamosus, Schizophyllum commune fungi were investigated. The change in ORP value of [Fe(CN)6]3–/[Fe(CN)6]4– mediatory system was used to detect AOA. Results concluded that Agaricus bisporus and Pleurotus ostreatus show the highest AOA, while Hypholoma fasciculare has the highest phenolic content. The phenolic content did not show any correlation with AOA, leading us to conclude that there are other antioxidant compounds present in the extracts.